2018
DOI: 10.3389/fnins.2018.00399
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of D-Amphetamine Induces Distinct Alterations in Behavior and Metabolite Levels in 129Sv and Bl6 Mouse Strains

Abstract: The main goal of the study was to characterize the behavioral and metabolomic profiles of repeated administration (for 11 days) of d-amphetamine (AMPH, 3 mg/kg i. p.), indirect agonist of dopamine (DA), in widely used 129S6/SvEvTac (129Sv) and C57BL/6NTac (Bl6) mouse strains. Acute administration of AMPH (acute AMPH) induced significantly stronger motor stimulation in Bl6. However, repeated administration of AMPH (repeated AMPH) caused stronger motor sensitization in 129Sv compared acute AMPH. Body weight of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…A prior study found that methamphetamine exposure reduced the levels of glucose in the plasma of humans [16]. Another study reported an increase in the levels of leucine in mice exposed to repeated administration of d-amphetamine [17]. These findings indicate that exposure to drugs of abuse can induce impairments in protein expressions or functions that regulate the metabolism of glucose and other metabolomics biomarkers.…”
Section: Introductionmentioning
confidence: 85%
“…A prior study found that methamphetamine exposure reduced the levels of glucose in the plasma of humans [16]. Another study reported an increase in the levels of leucine in mice exposed to repeated administration of d-amphetamine [17]. These findings indicate that exposure to drugs of abuse can induce impairments in protein expressions or functions that regulate the metabolism of glucose and other metabolomics biomarkers.…”
Section: Introductionmentioning
confidence: 85%
“…Particularly in the studied serum samples, a number of amino acids, acyl-carnitines, intermediates of the tricarboxylic acid cycle (TCA), bile and fatty acids have been identified as affected by GHB. The majority of these endogenous compounds relates to energy metabolism in the broadest sense and have also been described in relation to consumption of other DOAs [ 20 , 23 , 35 , 36 , 37 , 38 ]. As such, their suitability as biomarkers for identification of GHB in particular seems questionable, as first the observed fcs were small, particularly considering the highly controlled conditions of the study, and second they seem unlikely to allow differentiation of GHB intake from other DOAs.…”
Section: Discussionmentioning
confidence: 99%
“…Vanaveski et al observed increases of medium-chain acyl carnitines after repeated amphetamine administration in 129Sv mice. From the elevation of the ratio between long chain acyl carnitines to carnitine, the authors also proposed an increased participation of acyl carnitines to account for an additional energy demand [49]. It is also known that immune cells such as leukocytes are enriched in carnitines.…”
Section: Acyl Carnitinesmentioning
confidence: 99%